2016
DOI: 10.18805/ag.v37i4.6459
|View full text |Cite
|
Sign up to set email alerts
|

Sowing methods and varying seed rates of cowpea on production potentialof sorghum, sudan grass hybrid and cowpea: A review

Abstract: Forage requirement of livestock is generally met through low quantity and quality of crop residues often not enough for maintenance of animal health and productivity in India. Cereal-legume intercropping has been recognized as a beneficial crop production system for higher fodder production per unit area per unit time, especially, under rainfed conditions. Sorghum sudan grass hybrid and cowpea are some of the potential fodder crops which can provide good nutrition to livestock with higher forage yields and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Intercropping is the practice of cultivating two or more crops simultaneously on the same piece of land during the same time span (Guleria and Kumar 2016). It is characterized by rotation and diversification in time and space dimensions (Crusciol et al 2011;Biabania et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping is the practice of cultivating two or more crops simultaneously on the same piece of land during the same time span (Guleria and Kumar 2016). It is characterized by rotation and diversification in time and space dimensions (Crusciol et al 2011;Biabania et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…High-quality sorghum × sudangrass seed can effectively promote the development of animal husbandry, and germination percentage is one of the most routine indicators used to test seed quality (Basaram et al, 2017;Guleria & Kumar, 2018). Some studies have shown that longterm storage of sorghum × sudangrass seed affects its vigor and germination percentage (Gunjan & Naveen, 2016). Therefore, accurately determining the quality of sorghum × sudangrass seed can promote the continued development of animal husbandry (Dann et al, 2005).…”
Section: Crop Sciencementioning
confidence: 99%